Evaluating the accessibility and visibility of Quranic websites - Abu Bakar, Ahmad Bakeri (2010)
With the introduction of the World Wide Web and graphical browsers in the 1990s the Internet has become widely accessible and many people have grabbed the idea of using it for their multifarious purposes and agenda. They have established all types of websites to foster their mission and visions. They recognize that Internet can enhance their scale of communication through the websites as the Internet is capable of delivering large quantities of information in a speedy manner to the public. It is not surprising therefore that Muslims believe that the websites are the most useful platform to disseminate Islamic knowledge and information. The most important website that Muslims interact with is the Holy Quran website. Higher quality websites tend to attract more links and rendered those websites as highly visible. Using a software, Alexa, it is possible to gauge the volume of web traffic in order to determine the visibility of the website. In this paper Alexa is applied to study the visibility of Quranic websites. Nine quranic websites were investigated. It was found that the website, almushaf.com is the most visible website. It is futile to have a website that is difficult to access by users owing to non compliance with the accessibility guidelines. To check whether a particular Al-Quran website conforms or not to the accessible guidelines a software, A-Prompt could be used. The A-Prompt is able to examine the Al-Quran websites for barriers to accessibility, and at the same time is able to perform automatic repairs of the respective websites. Applying A-Prompt it was found that the most inaccessible website is the qurancomplex.org.